1989
DOI: 10.1017/s0305000900010448
|View full text |Cite
|
Sign up to set email alerts
|

Form and function in the acquisition of Korean wh-questions

Abstract: In this paper the order in which wh-questions are acquired in the production and comprehension of two Korean children, aged 1;8–2;8 and 1;10–2; 10, is analysed and compared with the available crosslinguistic data. Consistencies in acquisition order are hypothesized to be based on universals of cognitive development, which constrain the comprehension and production of wh-forms and influence the order in which mothers introduce them, and on functionally based similarities in the input of form/function pairs acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 17 publications
0
30
0
1
Order By: Relevance
“…(cf. Wode, 1974;Felix, 1976;Labov and Labov, 1978;Lightbown, 1978;Bloom et al, 1982;Stromswold, 1988;Clancy, 1989;. In my analysis of the developing English of six Korean children, who were learning English as an L2 in an immersion context, I have found a similar developmental pattern.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…(cf. Wode, 1974;Felix, 1976;Labov and Labov, 1978;Lightbown, 1978;Bloom et al, 1982;Stromswold, 1988;Clancy, 1989;. In my analysis of the developing English of six Korean children, who were learning English as an L2 in an immersion context, I have found a similar developmental pattern.…”
Section: Introductionmentioning
confidence: 79%
“…Table 4 shows the age of each subject and the number of wh-words used with S-V or S-AUX inversion. Clancy (1989) examined the order of the acquisition of whquestions by two Korean children in the age ranges 1; 8-2; 8 and 1; 10-2; 10. She found that the sequence of wh-questions produced and comprehended by the Korean children was similar to that of English-speaking children.…”
Section: Data From Previous Researchmentioning
confidence: 99%
See 3 more Smart Citations